2006
DOI: 10.1016/j.virol.2006.01.044
|View full text |Cite
|
Sign up to set email alerts
|

The immunogenicity and efficacy against H5N1 challenge of reverse genetics-derived H5N3 influenza vaccine in ducks and chickens

Abstract: H5N1 avian influenza viruses are continuing to spread in waterfowl in Eurasia and to threaten the health of avian and mammalian species. The possibility that highly pathogenic (HP) H5N1 avian influenza is now endemic in both domestic and migratory birds in Eurasia makes it unlikely that culling alone will control H5N1 influenza. Because ducks are not uniformly killed by HP H5N1 viruses, they are considered a major contributor to virus spread. Here, we describe a reverse genetics-derived high-growth H5N3 strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 26 publications
2
61
0
1
Order By: Relevance
“…Through this treatment was observed that infl uenza virus detected in these treated samples demonstrated reduction or total elimination of the viral HA titers (Table 3 and These results are in concordance with the study in ducks developed in Sweden by Wallenstein et al (2006). Webster et al (2006), observed that after birds vaccination against infl uenza HPAI (H 5 N 1 ) that the remained alive were protected against infl uenza.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Through this treatment was observed that infl uenza virus detected in these treated samples demonstrated reduction or total elimination of the viral HA titers (Table 3 and These results are in concordance with the study in ducks developed in Sweden by Wallenstein et al (2006). Webster et al (2006), observed that after birds vaccination against infl uenza HPAI (H 5 N 1 ) that the remained alive were protected against infl uenza.…”
Section: Resultssupporting
confidence: 87%
“…Considering this knowledge of influenza interspecies transmission by ducks, Webster et al(2006), performed an experimental vaccination against HPAI (H 5 N 1 ) intending to immunize these transmitter avians. These authors verifi ed that after the virus challenge performed in these vaccinated ducks, all of them remained alive showing they were protected against the virus.…”
Section: Introductionmentioning
confidence: 99%
“…Mass vaccination against HPAI in Egypt was adopted on the basis of the predicted efficacy of H5N1 vaccines in a number of avian species (36)(37)(38)(39)(40) and the recommendation of FAO/OIE to use vaccination as part of a control strategy for HPAI. Furthermore, field trials of oil emulsion-whole-virus H5 vaccines have shown promise in controlling H5N1 influenza outbreaks in Vietnam and the People's Republic of China (41)(42)(43).…”
Section: Vaccinementioning
confidence: 99%
“…Thus, the minimum vaccination coverage needed in the sub-district poultry population would be 21%, 51% and 32%, respectively, and the maximum value (51%) should be used as target to completely bring the epidemic under control. It should be acknowledged that vaccine efficacy is never 100% (van der Goot et al, 2005;Swayne et al, 2006;Webster et al, 2006), so an extra amount of vaccination coverage should always be added, e.g., 10% (van der Goot et al, 2005;Savill et al, 2006;Tiensin et al, 2007). Two issues must be stressed.…”
Section: Discussionmentioning
confidence: 99%